Development of Front Office Digital Modules on Applications on Android for Practical Learning in Tourism Schools - Endah Fitriyani; Andreas Suwandi; Ghoitsa Rohmah Nurazizah (Diploma Travel Business, Faculty of Social and Political Science, Jember University, 2022)
Online learning during this Covid-19 Pandemic faces various obstacles, the lack of supporting internet network facilities in each area, and the lack of teaching materials, especially in digital modules, it gives teachers more assignments than providing learning materials in class. This phenomenon must be addressed immediately by creating an Android-based digital module that was used during classroom learning. The research method used is Research and Development (R&D) using the ADDIE (Analyze – Design – Development – Implementation – Evaluation) model. This Android-Based Interactive E-Module learning media can be used offline, designed and developed using software to convert word files into ePub extension files. This media consists of concept maps, material descriptions, learning videos, and interactive quizzes packed all in one form, hoping that students can be more active in the learning process in class. This discovery is expected to answer the goals of this research, which include creating digital e-modules in the front office learning at tourism schools